Harold and Maude - Islam, Yusuf 1948- (<<The>> Criterion Collection, 2012)
Countercultural director Hal Ashby tells the story of the emotional and romantic bond between a death-obsessed young man from a wealthy family and a devil-may-care, bohemian octogenarian. Equal parts gallows humor and romantic innocence, Harold and Maude dissolves the line between darkness and light along with the ones that separate people by class, gender, and age. The cult classic of its era, featuring indelible performances and a soundtrack by Cat Stevens
Original: USA 1971
DVD special features: new digital restoration ; optional remastered stereo soundtrack ; new audio commentary by Hal Ashby, biographer Nick Dawson and producer Charles B. Mulvehill ; illustrated audio excerpts of seminars by Ashby and writer-producer Colin Higgins ; new interview with songwriter Yusuf/Cat Stevens ; plus: a boklet featuring an essay by critic Matt Zoller Seitz; a 1971 "New York Times" profile of star Ruth Gordon; and two excerpted interviews, one from 1997 with star Bud Cort and cinematographer John Alonzo and one from 2001 with executive producer Mildred Lewis
Bildformat 1.85:1 (16:9)
Keywords: Man-woman relationships / Drama; May-December romances / Drama; Problem youth / Drama; Man-woman relationships; May-December romances; Problem youth; Altersunterschied; Schüler; Schwarzer Humor; Zweierbeziehung; Film; DVD-Video